The Relationship Between Perceptions About Consuming Cigarettes With The Intention Of Smoking In Adolescents At Upt Smpn 1 Bangsal Kabupaten Mojokerto - Faisal ibnu (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2017)
dear my editor this is my journal. thanks